Seroprevalence of Newcastle Disease in Kampong Chickensin Gianyar Regency Bali - Kencana, Gusti Ayu Yuniati; Kardena, I Made; Andini, Ni Putu Eka Hari (Journal of Veterinary and Animal Sciences, 2018)
Newcastle disease (ND) or Tetelo is one of the viral diseases in poultry that causes high mortality and significant economic losses in chicken farms. Newcastle Disease is endemic in Bali as well as in Gianyar. Kerta village is one of the villages in Payangan Subdistrict at Gianyar regency where its location is nearby to the centre of hi breed chicken breeding industry in Kintamani Subdistrict at Bangli Regency and is the poultry trade traffic way from Kintamani to Denpasar. This study aimed to determine the seroprevalence of ND in kampong chickens in the village of Kerta at Gianyar regency. Purposive serum samples were collected from 80 unvaccinated backyard chickens from four (4) banjar (Kerta, Pilan, Buhu, and Marga Tengah) in Kerta village. Serological tests using Hemagglutination (HA) and Hemagglutination Inhibition (HI) were performed to the sera samples. Twenty out of the 80 serum samples (25%) were ND positive. The proportion of ND seropositive in each banjar was: 35%, 30%, 30% and 5% at Kerta, Pilan, Buhu, and Central Marga banjar, respectively. Twelve out of the 20 seropositive samples (12/20 = 60%) had protective antibodies, whilst the remains were negative. It is concluded that the seroprevalence of ND disease in the kampong chickens in Kerta village was 25% with antibody titres of 22 to 29 HI units which derived from natural infection.